Literature Review : Medication Compliance in Tuberculosis Patients - Umi Kalsum; Tri Mayang Amita; Lisdiawati Lisdiawati; Sudirman Sudirman; Ahmad Yani (Riviera Publishing, 2025)
Tuberculosis (TB) remains one of the leading global health challenges, with a high incidence of infection, widespread drug resistance, and significant morbidity, especially in low- and middle-income countries. Despite advancements in diagnostic tools, treatment regimens, and global policy support, adherence to TB medication remains a critical issue. This study aims to examine the factors influencing medication adherence among TB patients and assess the effectiveness of interventions designed to improve compliance. The research utilizes a literature review methodology, analyzing secondary data obtained from 15 journals and articles published between 2019 and 2024. The findings indicate that knowledge, family support, and healthcare access are key in improving TB treatment adherence. Integrating community-based interventions and educational programs has positively enhanced patient compliance. Additionally, addressing socio-economic factors such as poverty and inadequate healthcare access is essential in reducing TB incidence and preventing drug-resistant strains. The study emphasizes the importance of continuous monitoring, patient education, and support to ensure effective TB control and treatment. The results contribute to the development of targeted strategies for improving TB treatment adherence, particularly in regions with high TB burden.